The Impact of Educational Intervention to Increase Self Efficacy and Awareness for the Prevention of Domestic Violence Against Women - Mohammad Hossein Taghdisi; Marzieh Latifi; Mohammad Eshagh Afkari; Maryam Dastoorpour; Fatemeh Estebsari; Fiesal Jamalzadeh (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective:Violence against women are commonly seenthroughout the world. Studies showed that violence is related to self-efficacy. Therefore, this study was aimed to determine the effect of an educational intervention to increase self-efficacy and awareness for the prevention of domestic violence against women in the Gorgan city, Iran. Methods: This quasi-experimental study was designed with pre-and post-test on 91 married women under the aegis ofthe Imam Khomeini Relief Foundation (IKRF) in Gorgan in winter and spring of 2012-2013. Tools for gathering data includeddemographic information, General self-Efficacy questionnaire and a questionnaire about awareness of violence. Based on the results of the pretest, the educational contentwas prepared. Post-test was conducted 40 days later, after 3 educational sessions. Using SPSS16and analytical test such as the paired t-test data were analyzed. Results: The mean age of subjects were 37.37±12.13 years. The scores means of self-efficacy (p<0.001) and awareness (p<0.001) before and after the intervention were statistically had significant difference. Therefore, it seems thateducational program was effective in the promotion of the variables means. Conclusion: To decrease thedomestic violence against women, increasing women's self-efficacy and awareness through educational classes and proper planning is recommended. Paper Type: Research Article.